Mesentery-Sparing Technique: a New Intracorporeal Approach for Urinary Diversion in Robot-Assisted Radical Cystectomy - Eliney Ferreira Faria; Carlos Vaz de Melo Maciel; Pablo Almeida Melo; Marcos Tobias-Machado; Roberto Dias Machado; Rodolfo Borges dos Reis; Rodrigo José Costa-Gualberto (International Brazilian Journal of Urology, 2024)
ABSTRACT Background Robotic-assisted radical cystectomy (RARC) with intracorporeal urinary diversion (ICUD) is associated with significant morbidity and mortality. We present an alternative technique that preserves the complete mesenteric vascularization during the isolation of the intestinal segment used in ICUD, including distal vessels. This approach aims to minimize the risk of ischemia in both the ileal anastomosis and the isolated loop at the diversion site. Methods This cohort study included 31 patients, both male and female, who underwent RARC with ICUD from February 2018 to November 2023, performed by a single surgeon. Intraoperative and postoperative complications data were retrieved for analysis, employing our proposed mesentery-sparing technique in all cases. The primary endpoint was the incidence of intraoperative and postoperative complications directly attributable to the mesentery-sparing approach in ICUD. Secondary endpoints included other postoperative variables not directly related to mesentery preservation, such as the incidence of postoperative ileus requiring parenteral nutrition and the duration of hospitalization. Results None of the patients experienced intraoperative or postoperative complications directly related to mesentery-sparing, such as intestinal fistulae or internal hernias. The median duration of hospitalization was 6 days, and postoperative ileus necessitating total parenteral nutrition occurred in 19% of the patients. Minor complications (Clavien–Dindo grades I-II) accounted for 27.6% of the cases and major complications (grades III-V) accounted for 20.6%. Conclusion The mesentery-sparing technique outlined herein offers an alternative method for preserving the vascularization of intestinal segments and reducing the risk of intestinal complications in ICUD during RARC.